2012
DOI: 10.3892/etm.2012.576
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ABCA1 in human carotid atherosclerotic plaques

Abstract: Abstract. The ATP-binding cassette transporter A1 (ABCA1) is an important effector in the regulation of cholesterol efflux from cells. In this study, we assessed the role of ABCA1 in human carotid atherosclerotic plaques (CAPs). We found that ABCA1 and retinoid X receptor α (RXRα) mRNAs were significantly increased in the atherosclerotic plaques compared to control arteries. The increased ABCA1 mRNA correlated with that of RXRα in plaques. According to the modified American Heart Association plaque classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Liu et al 21 further noted that more advanced plaques (AHA plaque types III-VI) have lower ABCA1 protein expression compared with plaque types I and II, which are early lesions. Although our study contains only patients with advanced lesions, it is possible that fibroatheroma plaques express less ABCA1 than calcific or mainly fibrous plaques, whereas there is no difference in HDL, ApoAI, or C-reactive protein between patients with different AHA type V subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 21 further noted that more advanced plaques (AHA plaque types III-VI) have lower ABCA1 protein expression compared with plaque types I and II, which are early lesions. Although our study contains only patients with advanced lesions, it is possible that fibroatheroma plaques express less ABCA1 than calcific or mainly fibrous plaques, whereas there is no difference in HDL, ApoAI, or C-reactive protein between patients with different AHA type V subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…One member of these multidrug transporters, ABCG2, has been shown to play a major role in the protection of stem cells against toxic compounds. In addition, the ABCB6 protein has been indicated to play a major role in the defense against toxic heme derivatives, while the ABCA1 protein has a key role in the extrusion of excess cellular lipid derivatives, especially cholesterol (see refs (4)(5)(6)(7)(8)(9) ).…”
Section: Supplementary Tablementioning
confidence: 99%
“…Although several prior studies have compared ABCA1 levels between atherosclerotic plaques and healthy control tissues, our study demonstrates the significance of ABCA1 in carotid plaque rupture. For example, Albrecht et al [ 35 ] and Liu et al [ 36 ] reported that ABCA1 expression, which facilitates cholesterol efflux from cells, has different patterns at the mRNA and protein levels. The mRNA level of ABCA1 was higher, while its protein level was lower, in atherosclerotic plaques than in control tissues [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Albrecht et al [ 35 ] and Liu et al [ 36 ] reported that ABCA1 expression, which facilitates cholesterol efflux from cells, has different patterns at the mRNA and protein levels. The mRNA level of ABCA1 was higher, while its protein level was lower, in atherosclerotic plaques than in control tissues [ 35 , 36 ]. Our results add to the existing evidence, demonstrating that ABCA1 level is different between ruptured and non-rupture plaques.…”
Section: Discussionmentioning
confidence: 99%